2007
DOI: 10.1111/j.1468-0009.2007.00483.x
|View full text |Cite
|
Sign up to set email alerts
|

Using Population Segmentation to Provide Better Health Care for All: The “Bridges to Health” Model

Abstract: The model discussed in this article divides the population into eight groups: people in good health, in maternal/infant situations, with an acute illness, with stable chronic conditions, with a serious but stable disability, with failing health near death, with advanced organ system failure, and with long-term frailty. Each group has its own definitions of optimal health and its own priorities among services. Interpreting these population-focused priorities in the context of the Institute of Medicine's six goa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
142
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(143 citation statements)
references
References 2 publications
1
142
0
Order By: Relevance
“…The methods used to identify the sources of high expenditures have taken broad approaches in which the focus tends to be on all users of the health care system, with costs categorized by provider type or setting 8,9 . Canadian data along these lines have shown that cancer is one of five diagnostic conditions with the largest hospital care expenditures 10 .…”
Section: Introductionmentioning
confidence: 99%
“…The methods used to identify the sources of high expenditures have taken broad approaches in which the focus tends to be on all users of the health care system, with costs categorized by provider type or setting 8,9 . Canadian data along these lines have shown that cancer is one of five diagnostic conditions with the largest hospital care expenditures 10 .…”
Section: Introductionmentioning
confidence: 99%
“…'Segmentation', a term used in quality improvement, is a useful way of thinking about managing the postoperative patient [33]. If we divide postoperative care into two segments, ward care and critical care, we can work firstly on ensuring that patients go into the correct area of care.…”
mentioning
confidence: 99%
“…Estimates from the US Centers for Medicare and Medicaid Services suggest that chronic disease accounts for nearly 76% of all health care expenditures. 2 Any effort to steer the US health care system toward a more sustainable path of expenditures must tackle the enormous impact of chronic illnesses.…”
Section: Introductionmentioning
confidence: 99%